2003
DOI: 10.1007/s00424-003-1170-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic moderate hypoxia during in ovo development alters arterial reactivity in chickens

Abstract: We previously observed arterial sympathetic hyperinnervation and endothelial dysfunction in the chicken embryo after exposure to chronic hypoxia. We now investigate whether changes in arterial properties could also be observed at 14-15 weeks of life. Eggs of White Leghorn chicken were incubated under normoxic or moderately hypoxic (15% O2 from days 6-19 of a 21-day incubation) conditions. Experiments were performed at 14-15 weeks of life under standard conditions (Hm: males exposed to hypoxia; Hf: females expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 41 publications
3
44
1
Order By: Relevance
“…However, data in the present study show that in vivo assessment in adult offspring from hypoxic pregnancy provides no evidence of either an increase in peripheral vascular resistance or systemic hypertension. This finding is corroborated by further evidence of no hypertension in highland residents, 40 neonatal sheep from high altitude pregnancy, 35 adult chickens subjected to hypoxia in ovo, 32 or adult rats following prenatal hypoxia. 37, 41 Despite no evidence of any changes in basal arterial blood pressure, this study revealed significant programming on the autonomic control of arterial blood pressure in adult offspring Values are mean ± SEM for baroreflex function in 4-month-old male offspring from Normoxic (N; n=8), Hypoxic (H; n=9), Hypoxic+Vitamin C (HC; n=7) and Normoxic+Vitamin C (NC; n=7) pregnancies.…”
Section: Discussionmentioning
confidence: 54%
“…However, data in the present study show that in vivo assessment in adult offspring from hypoxic pregnancy provides no evidence of either an increase in peripheral vascular resistance or systemic hypertension. This finding is corroborated by further evidence of no hypertension in highland residents, 40 neonatal sheep from high altitude pregnancy, 35 adult chickens subjected to hypoxia in ovo, 32 or adult rats following prenatal hypoxia. 37, 41 Despite no evidence of any changes in basal arterial blood pressure, this study revealed significant programming on the autonomic control of arterial blood pressure in adult offspring Values are mean ± SEM for baroreflex function in 4-month-old male offspring from Normoxic (N; n=8), Hypoxic (H; n=9), Hypoxic+Vitamin C (HC; n=7) and Normoxic+Vitamin C (NC; n=7) pregnancies.…”
Section: Discussionmentioning
confidence: 54%
“…Hypoxia also has varying degrees of effect on the morphology and performance of the heart and systemic vasculature, ranging from no effect to profound disturbance (Asson-Batres et al, 1989;Richards et al, 1991;Burton and Palmer, 1992;Altimiras and Phu, 2000;le Noble et al, 2000;Dzialowski et al, 2002;Rouwet et al, 2002;Villamor et al, 2002;Ruijtenbeek et al, 2003;Villamor et al, 2004;Chan and Burggren, 2005;Zhang and Burggren, 2012). Corresponding with these cardiorespiratory phenotypic modifications are changes in overall metabolic rate, typically measured as oxygen consumption.…”
Section: Hypoxia Hypercapnia and Avian Critical Windowsmentioning
confidence: 99%
“…Interestingly, albumen removal also results in adult hens with modified DNA methylation and long-term alterations in the hepatic transcriptome (Willems et al, 2016). The extraction of a percentage of the egg contents reduces embryonic growth and results in a low hatching weight, but apparently without any vascular consequences (Ruijtenbeek et al, 2003).…”
Section: Fetal Programming -Beyond Mammals To Birdsmentioning
confidence: 99%
“…Hypoxia alters the endothelial properties of fetal pulmonary (23), fetal carotid (16,17), cerebral (24), and femoral arteries (10,25,26). The effect of chronic hypoxia on fetal tissue eNOS gene expression is variable among different cell types.…”
Section: Articlesmentioning
confidence: 99%
“…*P < 0.05; **P < 0.01, maternal hypoxia (black bars) as compared with control (white bars). sequence of the human and bovine eNOS gene (30)(31)(32), the changes in blood flow occurring during fetal hypoxemia may alter arterial shear stress (26), which in turn can modulate the expression and activity of eNOS (33). One of the well-studied signaling pathways activated during endothelial response to shear stress is the cascade consisting of G-protein → phospholipase C/Ca 2+ → protein kinase C → c-fos/c-jun → activator protein 1 site-dependent transcription; this pathway is operative in the elevation of eNOS expression by shear stress.…”
Section: Articlesmentioning
confidence: 99%